Some Adaptive Contributions to Logics of Formal Inconsistency - Batens, Diderik (New Directions in Paraconsistent Logic, 2015)
Some insights were gained from the study of inconsistency-adaptive logics. The aim of the present paper is to put some of these insight to work for the study of logics of formal inconsistency. The focus of attention are application contexts of the aforementioned logics and their theoretical properties in as far as they are relevant for applications. As the questions discussed are difficult but important, a serious attempt was made to make the paper concise but transparent.